First skeletal remains of the giant sawfish Onchosaurus (Neoselachii, Sclerorhynchiformes) from the Upper Cretaceous of northeastern Italy. (January 2017) - Amalfitano, Jacopo; Giusberti, Luca; Dalla Vecchia, Fabio Marco; Kriwet, Jürgen
Abstract: Sclerorhynchiform sawfishes are a diverse and extinct clade of elasmobranchs that is restricted to the Cretaceous. Most taxa are known only by isolated rostral spines, whereas skeletal remains are rare and have been reported from a small number of Upper Cretaceous localities. Here, we describe skeletal remains of the giant sclerorhynchiform Onchosaurus pharao for the first time, which provides new morphological information. The single specimen comes from middle-basal upper Turonian strata of the Lessini Mountains in northeastern Italy and represents the first record of this genus from Italy. The specimen consists of unidentifiable cranial remains, several diagnostic rostral spines, the rostrum with fragments of tessellated calcified cartilage, and 87 disarticulated vertebrae. The rostrum preserves the characteristic sensory system of sclerorhynchiforms. It is devoid of any lateral sockets indicating that rostral spines were attached laterally to its surface. This pattern is identical to most sclerorhynchiforms and extant pristiophoriformes implying also similar replacement patterns as in most other sclerorhynchiforms with the exception for Schizorhiza . Additionally, the bases of two longitudinally arranged rows of ventral rostral spines are identifiable concurring with patterns seen in Sclerorhynchus . The axial skeleton is partly preserved. Re-arranging the disarticulated vertebrae according to their life position in combination with measures of the size and thickness of preserved vertebral centra, and the ratio rostrum length/body size depending on the number of vertebral centra indicate that the specimen was ca. 450 cm long. Growth rings in the vertebral centra show that the specimen was about four years old and thus probably not yet fully sexual mature when it died. This age assumption corresponds well with the calculated size when compared with complete skeletons of extinct sclerorhynchiforms and extant pristiforms. The size of the specimen and its occurrence in hemipelagic rocks corroborates previous assumptions that this sclerorhynchiform was a large and pelagic sawfish.